خـارج الجسـم الحـي (Eustoma grandiflorum (Raf). Shinn.) Lisianthus النبات الدقيق - محمد, حسام سعد الدين (Al-Nahrain Journal of Science, 2011)
A complete protocol for Lisianthus (Eustoma grandiflorum) micropropagation was designed. Several experiments were conducted. Sodium hypochlorite NaOCl was tested for explants surface sterilization, the effect of cytokinins, Benzyl adenine (BA) or 6-Furfural amino purine )KIN( and the auxins, Indol butyric acid (IBA) or Indol-3-acetic acid (IAA) on shoots initiation, Multiplication, rooting and acclimatization stages. Results indicated that 1.5% of sodium hypochlorite was effective in disinfecting explants. Nodal segments were better than shoot tips in their response to in vitro culture. BA at 0.3 mg/l gave the highest average of shoots number (6.2) from nodal segments. Shoots number and length increased to 7.2 and 2.03 cm respectively when 0.1 mg/l was added to the initiation medium. The height multiplication rate (8.4 shoots with 3.41cm in length) was achieved when shoots were transferred to a medium supplemented with 1.0 mg/l BA and 0.5 mg/l IBA. In rooting stage 60% of shoots were rooted in a medium supplemented with 1.0 mg/l IBA with 4.6 roots and 1.4 cm in length. Rooting was improved up to 90% by increasing sucrose concentration up to 45 g/l. Roots number and length increased to 9.7 and 4.8 cm respectively. Acclimatization of plantlets was achieved using a mixture of river sand and peat moss (2:1) (v:v) with 90% plantlet survival. According to these results, Lisianthus micropropagation can be carried out using the protocol described above.